Efektivitas EMI Shielding: Komparasi Kopolimer dengan Partikel Logam dan Aluminium untuk Perlindungan Satelit Militer dari Gangguan Sinyal - Sinaga, Farhan Syaifullah; Aritonang, Sovian (Fakultas Teknik UMSU, 2025)
Electromagnetic interference (EMI) is a serious threat to the stability and security of military satellites that play an important role in communication, surveillance, and reconnaissance. However, there are various threats such as EMI that can cause damage to electronic devices and disrupt data transmission. Aluminum has long been used as an EMI shielding material due to its good conductivity and relatively low cost, but its effectiveness decreases at high frequencies, making it less ideal for applications that require shielding over a wide frequency spectrum. This study evaluates the effectiveness of copolymers with conductive fillers (such as MXene and Carbon Nanotubes) and metal particles (nickel and copper) compared to aluminum as EMI shielding materials in military satellite applications. Tests were carried out in the frequency range of 0.1 to 3 GHz using the anechoic chamber method and using a vector network analyzer (VNA) to measure transmission and reflection parameters. The results showed that copolymers with conductive fillers achieved Shielding Effectiveness (SE) of 30–50 dB at high frequencies, while metal particles such as nickel and copper showed SE of 40–60 dB at low to mid frequencies, while aluminum had SE of up to 70 dB but limited to low frequencies. Copolymers with metal particles, especially with MXene fillers, provide optimal performance over a wide frequency spectrum with additional advantages of lighter weight and good corrosion resistance. These findings demonstrate the potential of copolymers with conductive fillers as more effective and efficient EMI shielding materials for military satellite applications in space environments, with the ability to shield high and low frequency spectrums comprehensively.